Housing Finance : Investment Opportunities for Pension Funds - World Bank Group (World Bank, Washington, DC, 2019)
The global housing deficit in both developed and developing countries is increasing – driven by demographic and other mega-trends including urbanization and income inequality. Global pension fund assets, on the other hand, are both growing and increasingly looking for long-term, productive investments. There are multiple avenues through which pension funds can invest in the housing sector.